2007
DOI: 10.3181/0703-rm-83
|View full text |Cite
|
Sign up to set email alerts
|

13-cis-Retinoic Acid Alters Intracellular Serotonin, Increases 5-HT1AReceptor, and Serotonin Reuptake Transporter LevelsIn Vitro

Abstract: In addition to their established role in nervous system development, vitamin A and related retinoids are emerging as regulators of adult brain function. Accutane (13-cis-retinoic acid, isotretinoin) treatment has been reported to increase depression in humans. Recently, we showed that chronic administration of 13-cis-retinoic acid (13-cis-RA) to adolescent male mice increased depression-related behaviors. Here, we have examined whether 13-cis-RA regulates components involved in serotonergic neurotransmission i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 51 publications
(68 reference statements)
2
45
1
5
Order By: Relevance
“…Our finding of higher 5-HT 1A in NRM MDD is replicable and also consistent with post-mortem data [26], as well as data from other modalities [29,37,41]. Furthermore, it lends additional support to the hypothesis of higher 5-HT 1A in depression and agrees with the purported model underlying selective serotonin reuptake inhibitors (SSRIs) [42,43].…”
Section: Future Directions and Implicationssupporting
confidence: 88%
“…Our finding of higher 5-HT 1A in NRM MDD is replicable and also consistent with post-mortem data [26], as well as data from other modalities [29,37,41]. Furthermore, it lends additional support to the hypothesis of higher 5-HT 1A in depression and agrees with the purported model underlying selective serotonin reuptake inhibitors (SSRIs) [42,43].…”
Section: Future Directions and Implicationssupporting
confidence: 88%
“…This indicates that they Several studies have shown that the molecular components needed for retinoic acid signalling are expressed in the adult brain, suggesting that retinoids could play a role in affective disorders. [21][22][23][24][25][26][27][28][29] In young adult mice, chronic administration of isotretinoin induced depression related behaviours. 22 These changes were not seen in adult rats.…”
Section: Discussionmentioning
confidence: 99%
“…However, high doses of retinoic acid are currently being used for the prevention and treatment of certain cancers and skin diseases (Germain et al, 2006). Because such doses may have side-effects on brain function (O'Reilly et al, 2007;Bremner and McCaffery, 2008), it will be of interest to investigate further their effects in the adult brain.…”
Section: Discussionmentioning
confidence: 99%